1969
DOI: 10.1042/bj1110487
|View full text |Cite
|
Sign up to set email alerts
|

A phosphorylation site in brain and the delayed neurotoxic effect of some organophosphorus compounds

Abstract: 1. It is proposed that part of a neurotoxic dose of di-isopropyl phosphorofluoridate will be covalently bound in vivo to a specific component in the brain and spinal cord as the initial biochemical event in the genesis of the lesion. 2. A test system in vitro was devised that removes many di-isopropyl phosphorofluoridate-binding sites and indicates that the specific component may be a protein present in brain at a concentration comparable with that of the cholinesterases. 3. The site was found to be present an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

1978
1978
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(34 citation statements)
references
References 13 publications
0
32
0
2
Order By: Relevance
“…The phosphorylation of an enzyme (neuropathy target esterase; NTE) in nerve tissue is considered to be responsible for the polyneuropathy [72,73]. Neuropathy target esterase is a membrane-bound protein with high esterase catalytic activity whose physiological function is not known.…”
Section: Delayed Polyneuropathymentioning
confidence: 99%
“…The phosphorylation of an enzyme (neuropathy target esterase; NTE) in nerve tissue is considered to be responsible for the polyneuropathy [72,73]. Neuropathy target esterase is a membrane-bound protein with high esterase catalytic activity whose physiological function is not known.…”
Section: Delayed Polyneuropathymentioning
confidence: 99%
“…NTE was originally identified and defined by its ability to both bind a radiolabelled OP and hydrolyse a (non-physiological) ester substrate [7,8]. By the mid-1970s, pioneering work by Johnson showed that inhibition by OPs of NTE's esteratic activity per se did not itself initiate neuropathy ; the latter required a rapid secondary intramolecular change in the neutrally charged covalently bound OP, which left a negatively charged form of the OP still attached to the active-site serine of NTE [9].…”
Section: Introductionmentioning
confidence: 99%
“…Certain fluoro-organophosphorus compounds are known to ,cause deLayed neurotoxicity (1,2,5,12,13). Hexane (20) and other hydrocarbon solvents (8) may also cause ,polyneuropa;thy.…”
Section: Discussionmentioning
confidence: 99%